Resisting Timber Joint Performance of Karo Wooden Building - Khairussa’diah Khairussa’diah; Yulianto P. Prihatmaji (Wood Research Journal, 2019)
Batak Karo is one of the ethnic group that exists in North Sumatra. Wooden house of Batak Karo called with Siwaluh Jabu. This wooden house has a structure system of pillars on top of stone foundations. This type of foundation is able to improve the performance of the overall structure due to lateral style caused by the earthquake. This research was conducted to know the behaviour of the structure of a wooden Batak Karo home especially the restoration of wooden style joints by comparing the results of a laboratory test, numerical analysis and analysis with SAP2000. Experimental testing in the lab do the test objects as much as 3 pieces. Testing by giving a cyclic load with a capacity of 10 tons in each of the test object to damaged object. Then conduct an evaluation the behavior of the structure consist of failure modes and moment-rotational angle relationship. After the experimental test was completed, the analysis continued with validate test results with laboratory of numerical analysis. Then conducted an analysis of the power structure by using SAP2000 program to know the power of elements against the maximum tension. The analysis conducted on the overall structure of the system and the structure of mast above the foundation stone. The program was conducted with input data: the work load, etc. As the output from these programs is the element force, etc. The final results of this program are the weaknesses and advantages of structural system observed from wooden Batak Karo.